Biological Characteristics of Some Widely Distributed Brotherhood Species in Fergana Valley - Sh.Q. Yuldasheva; D.Mo’ydinova (Zien Journals, 2024)
In this article highlights of biological characteristics of some widely distributed brotherhood species in Fergana valley.
Keywords: Biological characteristics; brotherhood species; dragonflies